Methodological results of horn hardness measurements on Hungarian Gray Cattle bulls - Demény, Márton; Gera, István; Bodó, Imre; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2012)
Longevity is getting important in cattle breeding, which determines profitability. Long useful life first of all depends on appearance, especially on the quality of udder and foot structure. In the case of the quality properties of foot structure the claw horn hardness is concerned to be very important. Hungarian Gray Cattle can be the base of longevity researches because of its long useful life expectancy and good calf-rearing ability. Nevertheless during horn conformation researches on Hungarian Gray Cattle we have to investigate claw horn and horn hardness as well, which is a „fighting weapon” and has similar properties with claw horn. We managed to get samples from bulls from the end of their horns. These bulls were bred in Apaj from the herd of Szomor Dezső (MSZ-005). Results showed that the location of measuring has no effect on horn hardness (F = 1,195, df = 2, P = 0,317, α = 0,05), however polishing has altered sample hardness (F = 45,93, df = 1, P = 0,00, α = 0,05).